TINJAUAN YURIDIS LEMBAGA PENAHANAN TERHADAP PELAKSANAAN PERINTAH PENAHANAN HAKIM YANG TERDAPAT DALAM PUTUSAN PENGADILAN - M. Ali Said Kurniawan Said (Scholar Center, 2021)
The purpose of this study is to find out first, how the arrangements of detention institutions to ensure legal certainty on the implementation of the judge's detention order (Ordering the defendant to be detained immediately) contained in the Court's decision. Second, to find out the juridical implications for the defendant and the Public Prosecutor on the implementation of the judge's detention order contained in the Court's decision. The method used in this research is a normative juridical research method. The results of the study said that in the public interest detention can be done with strict conditions. Therefore, the detention made against the defendant is limited by the rights of the suspect/defendant and the legislation is carried out in a limitative manner in accordance with the provisions of the Criminal Code. The implementation of the judge's detention authority in judicial practice there is ambiguity of legal norms because it is not regulated in the Criminal Code on the rules of judge's detention authority after the verdict is pronounced by the judge so that it gives rise to different interpretations from the point of view of the Public Prosecutor and Defendant's Legal Adviser. The judge's detention order is in accordance with the Instructions from the Attorney General of the Republic of Indonesia in his letter Number: R-89/EP/Ejp/05/2002 dated 06 May 2002 states: if there is an order to detain the defendant contained in the decision, then the Public Prosecutor must immediately execute it , although the decision does not yet have permanent legal force, because the implementation of the detention of the defendant carried out by the Public Prosecutor does not execute the court's decision, but merely executes the Judge's order contained in the verdict, as referred to in article 197 paragraph (1) letter k KUHAP.